2020
DOI: 10.3389/fpsyg.2020.00388
|View full text |Cite
|
Sign up to set email alerts
|

The Attention Network Test Database: ADHD and Cross-Cultural Applications

Abstract: Attention is a central component of cognitive and behavioral processes and plays a key role in basic and higher-level functioning. Posner's model of attention describes three components or networks of attention: the alerting, which involves high intensity states of arousal; the orienting, which involves the selective direction of attention; and the executive control, which involves cognitive functions such as conflict resolution and working memory. The Attention Network Test (ANT) is a computerized testing mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 84 publications
2
44
2
Order By: Relevance
“…Although impaired alerting network is well-established in ADHD children (Arora et al, 2020), this phenomenon has been less frequently reported in adults with ADHD (e.g., Oberlin et al, 2005). For instance, our findings are inconsistent with those reported by Lundervold et al (2011), who found no difference in any attentional network between adults with ADHD and controls, despite we had similar statistical power and a more homogeneous sample than them (i.e., no participants with ADHD).…”
Section: Attentional Networkcontrasting
confidence: 99%
See 1 more Smart Citation
“…Although impaired alerting network is well-established in ADHD children (Arora et al, 2020), this phenomenon has been less frequently reported in adults with ADHD (e.g., Oberlin et al, 2005). For instance, our findings are inconsistent with those reported by Lundervold et al (2011), who found no difference in any attentional network between adults with ADHD and controls, despite we had similar statistical power and a more homogeneous sample than them (i.e., no participants with ADHD).…”
Section: Attentional Networkcontrasting
confidence: 99%
“…Extensive research has used the ANT/ANTI or some of its variants to analyze the attentional networks in ADHD. A recent meta-analysis including the ANT and the ANT child version (Rueda et al, 2004) compared 491 ADHD children with 402 typical developing controls in nine studies (Arora et al, 2020). They found the functioning of the alerting and executive networks-but not orienting-to be impaired in ADHD.…”
mentioning
confidence: 99%
“…In order to evaluate the existing literature that has explored attentional differences in bilingualism using the ANT, we used the attention network test (ANT) Database (Arora et al 2020). The ANT Database is a repository of all academic publications that have cited the original Fan et al (2002) paper and used the ANT or any of its variants in an experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Using the Hofstede Insights web-tool based on Hofstede et al (2010) we discovered that in four of these studies bilinguals were likely drawn from collectivist societies and monolinguals were likely drawn from individualistic societies. Whereas all four of these studies reported bilingual advantages, the confound opens the door to the possibility that these advantages are culturally rather than linguistically mediated (cf, Arora et al 2020;Paap et al 2015).…”
Section: Young Adultsmentioning
confidence: 99%
“…Accompanying group ns were also extracted. When Ms and SDs were not reported in the text or a table, we extracted these values from relevant plots with WebPlotDigitizer (Rohatgi, 2019), which is a validated tool for extracting numerical values from figures (Arora et al, 2020;Castrellon et al, 2020;Drevon et al, 2017;Kip et al, 2020;Lim et al, 2017). We note that there was one instance in which we extracted values using WebPlotDigitizer only to later receive the values from the authors (Young et al, 2017).…”
Section: Brain Outcomesmentioning
confidence: 99%